2015
DOI: 10.1371/journal.pone.0144295
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-122 Inhibits the Production of Inflammatory Cytokines by Targeting the PKR Activator PACT in Human Hepatic Stellate Cells

Abstract: MicroRNA-122 (miR-122) is one of the most abundant miRs in the liver. Previous studies have demonstrated that miR-122 plays a role in inflammation in the liver and functions in hepatic stellate cells (HSCs), which reside in the space of Disse. Here, we showed that the transient inhibition of PKR-activating protein (PACT) expression, by miR-122 or siRNA targeting of PACT, suppressed the production of proinflammatory cytokines, such as interleukin (IL)-6, monocyte chemoattractant protein-1 (MCP-1) and IL-1β, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…Cell death, including apoptosis, seems important in the progression of NAFLD and NASH (Figure 1 ). Recently, several inhibitors of apoptosis have been suggested as potential treatments for NASH (Table 1 )[ 112 - 124 ]. Clinical trials for the treatment of NASH are currently being conducted[ 125 ] and some are targeting apoptosis in NASH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death, including apoptosis, seems important in the progression of NAFLD and NASH (Figure 1 ). Recently, several inhibitors of apoptosis have been suggested as potential treatments for NASH (Table 1 )[ 112 - 124 ]. Clinical trials for the treatment of NASH are currently being conducted[ 125 ] and some are targeting apoptosis in NASH patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that pre-treatment with IRE1α inhibitor reduced pro-inflammatory cytokines production in tumor necrosis factor (TNF)-receptor-associated periodic fever syndrome (TRAPS) dermal fibroblasts (DFs) ( Harrison et al, 2018 ). On the other hand, these inflammatory cytokines were also the downstream target genes of miR-122 ( Hsu et al, 2012 ; Nakamura et al, 2015 ; Yin et al, 2016 ; Tang et al, 2017 ). In the present study, the result showed that STF-083010 evidently inhibited the upregulation of hepatic α-SMA, Col1α1 and Col1α2 in mice, but these also may be attributed to HSCs expression and the fact that STF-083010 alleviates liver injury by inhibiting CCl 4 -mediated hepatocyte death.…”
Section: Discussionmentioning
confidence: 99%
“…As some of these changes in NK‐cell markers showed similar changes on bulk CD8 + T cells and CD56 + NK T cells, the observed changes in the NK‐cell compartment might be the result of an overall decrease in immune activation upon a decline in HCV viral load. However, as miR‐122 has been implicated in immune regulation, direct effects of miR‐122 inhibition could also contribute to the changes in NK cells observed …”
Section: Discussionmentioning
confidence: 99%
“…However, as miR-122 has been implicated in immune regulation, direct effects of miR-122 inhibition could also contribute to the changes in NK cells observed. (25,26,32,33) Chronic CHC infection leads to dysfunctional ("exhausted") HCV-specific CD8 1 T cells. In patients successfully treated with IFN-free therapy, a restoration of the proliferative capacity of these HCV-specific CD8 1 T cells has been observed.…”
Section: Discussionmentioning
confidence: 99%